Current Situation and Development Trend of End-of-life Photovoltaic Module Treatment and Disposal - Shifa ZHOU; Guang HU; Zhaoyang LI; Qingfang ZOU; Zhiming ZHANG; Huabo DUAN; Sha LIANG; Jiakuan YANG (能源环境保护)
The adoption of clean energy, particularly solar energy, serves as a critical measure for achieving the dual-carbon goals. By the end of 2023, China′s cumulative installed solar capacity had reached 609 GW, with projections indicating a rise to approximately 5 000 GW by 2050. Consequently, the volume of decommissioned solar photovoltaic (PV) modules is expected to surge from 26000 tons to over 15 million tons by 2050. The recycling and disposal of these modules is a pivotal challenge for sustainable development in the solar energy industry. This study conducts a comprehensive analysis and comparative assessment based on literature reviews and experimental research, addressing the technological advancements and industrial expansion of solar PV systems, the generation characteristics of end-of-life PV modules, and recycling and processing technologies. The scope encompasses traditional crystalline silicon PV modules and emerging thin-film solar modules, particularly those dominated by perovskite-based technologies. This paper systematically reviews the recycling, disposal, and future prospects of PV modules. Among existing technologies, crystalline silicon solar cells are the most extensively researched and widely deployed, followed by thin-film solar cells, which have a relatively smaller market share. Meanwhile, emerging solar cell technologies, characterized by lower material costs and energy demands, have made significant progress in recent years. Furthermore, the study investigates control strategies for characteristic pollutants and critical elements in various waste PV modules, and proposes developmental directions for recycling technologies and pollution control methodologies for end-of-life PV modules. Findings reveal that PV module waste continues to be managed as conventional solid waste, despite its complex material composition and multi-component nature. These modules possess significant resource recovery potential, but their recycling processes face challenges such as high costs and low utilization rates. To achieve high-value recycling, appropriate pre-treatment of decommissioned PV modules is crucial. For instance, hierarchical processing methods facilitate effective separation, enabling the recovery of high-value materials. Although researchers have developed relevant recycling technologies and pollution control approaches, industry-specific standards and supportive policies are essential for large-scale implementation. Future efforts should focus on improving the efficiency and applicability of recycling and disposal methods to accommodate diverse PV module types. Stronger policy incentives are also essential. This research provides critical insights for advancing studies on the future development of the photovoltaic industry. It also addresses industrial scale recycling technologies for end-of-life PV modules. Moreover, it provides a foundational framework for the integrated management of solid waste generated by new energy systems. The outcomes underscore the necessity for systematic innovations in recycling infrastructure, economic incentive mechanisms, and regulatory frameworks to address the impending surge in PV module waste while maximizing resource recovery efficiency and minimizing environmental impacts across the product lifecycle.